Evaluasi Kualitas Website SEGO PETANI terhadap Kepuasan Pengguna Menggunakan WebQual 4.0 - Desi Lajar Sari; Nova Tri Romadloni (TIN: Terapan Informatika Nusantara, 2026)
This study aims to evaluate the quality of the SEGO PETANI website using the WebQual 4.0 method and analyze its effect on user satisfaction. The SEGO PETANI website is a digital platform designed to help farmers report pest and plant disease attacks in order to support the effectiveness of technology-based agricultural services. The research was conducted at Dinas Pertanian Pangan dan Perikanan Kabupaten Karanganyar involving 167 respondents who had used the SEGO PETANI website. This study employed a quantitative approach with a descriptive-verificative design and purposive sampling technique. Data were collected through questionnaires based on a five-point Likert scale developed from the dimensions of usability quality, information quality, and service interaction quality. Data analysis was performed using SPSS through validity testing, reliability testing, multiple linear regression, t-test, F-test, and coefficient of determination analysis. The results showed that the website quality was categorized as good, with average scores of 4.00 for usability quality, 4.03 for information quality, and 4.06 for service interaction quality. Website quality significantly affected user satisfaction with a coefficient of determination value of 71.1%. Service interaction quality was identified as the most dominant factor influencing user satisfaction. This study provides practical contributions as an evaluation material for improving digital agricultural services and academic contributions through the implementation of the WebQual 4.0 method in public service-based information systems.